2009
DOI: 10.1002/14651858.cd005332.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy and psychotherapy for body dysmorphic disorder

Abstract: Analysis 2.1. Comparison 2 Pharmacotherapy versus placebo (secondary outcomes), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 69 publications
1
44
0
5
Order By: Relevance
“…In addition, comorbidity rates are high for OCD and BDD, and the prevalence of BDD is elevated in firstdegree relatives of individuals with OCD [17]. Other lines of evidence suggest that BDD shows similarities with OCD in terms of its neural substrates [33] and preferential response to treatment with SSRIs and with CBT/ERP [34]. However, insight is typically much poorer in BDD than in OCD [32].…”
Section: Body Dysmorphic Disordermentioning
confidence: 99%
“…In addition, comorbidity rates are high for OCD and BDD, and the prevalence of BDD is elevated in firstdegree relatives of individuals with OCD [17]. Other lines of evidence suggest that BDD shows similarities with OCD in terms of its neural substrates [33] and preferential response to treatment with SSRIs and with CBT/ERP [34]. However, insight is typically much poorer in BDD than in OCD [32].…”
Section: Body Dysmorphic Disordermentioning
confidence: 99%
“…Also for skin picking (dermatillomania) effective treatments have been developed, which use among other things habit reversal and cognitive restructuring techniques [64,65]. For body dysmorphic disorder, effective behavioral therapies have been developed, which focus on exposure to (fear triggering) social stimuli, response prevention (for example looking at oneself in the mirror, omitting superfluous make-up) and changing irrational beliefs and cognitions about one's own appearance [66,67].…”
Section: Treatments Of Psychiatric Problems In Dermatological Practicementioning
confidence: 99%
“…Psychopharmacologic trials have mainly focused on selective serotonin reuptake inhibitors (SSRIs) such as citalopram [32], escitalopram [33], clomipramine [34], fluvoxamine [35,36], and fluoxetine [37], which seem to be effective at reducing BDD symptom severity [38].…”
Section: Effective Treatments For Individuals With Body Dysmorphic DImentioning
confidence: 99%
“…Recently, a meta-analysis showed that both pharmacotherapy (particularly SSRIs) and CBT were effective in treating BDD [38,39]. Interestingly, five of the nine psychotherapy studies had completion rates of 100%, indicating that CBT is very acceptable to individuals with BDD [39].…”
Section: Effective Treatments For Individuals With Body Dysmorphic DImentioning
confidence: 99%